Marketing of impressions in the tourism business - Chernishova, D. V.; Pererva, P. G. (My University, 2023)
It has been proven that in tourism the tools of impression marketing will contribute to the sustainable development of services for consumers of tourist services.
Маркетинг вражень у туристичному бізнесі
Keywords: tourism industry; business; impression marketing; market; enterprises